Keselamatan Makanan Menurut Perspektif Islam: Kajian Terhadap Pengambilan Makanan Berisiko - Mohamad, Musfirah Syahida; Man, Saadan; Ramli, Mohd Anuar (Jurnal Fiqh, 2015)
This study discusses an issue of food safety from the perspectives of Islamic law by focusing on consumption of high risk food. The consumption of several kind of foods is believed to be a cause to certain disease to human, in which to some extent, will affect human immune systems. Food safety is not only protecting food production process but it is also improving health and nutrition. It is consistent with the principle of halalan tayyiban food which can be described as clean, safe and nutritious food. This article attempts to examines the relationship between halalan tayyiban and food safety. This study is is conducted by method of library research as well as field research. This study finds out that consuming risky food may be categorized into different rulings (hukm) depending on a person’s health condition.